2021
DOI: 10.3390/microorganisms9050962
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Leishmaniasis in Algeria; Highlight on the Focus of M’Sila

Abstract: Algeria ranks second after Afghanistan for the incidence of cutaneous leishmaniasis (CL) worldwide. Here, we report a 34-years retrospective analysis of CL in Algeria and focused on the most affected region, the M’Sila province. All 66 cutaneous isolates corresponded to Leishmania (L.) major. Our study of the sandfly and rodent fauna further highlighted the high density of Phlebotomus papatasi and additional phlebotomine species of medical importance, not previously identified in M’Sila. Wild rodents belonging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Our study revealed that males were more affected by CL than females which agree with different studies [10][11][12][13][14][15][16][17]. However, our finding is analogized with the studies reported from Algeria, Istanbul, Turkey, and Larstan, South of Iran that excess in the frequency of CL cases among females than males [18][19][20]. In contrast to this, the studies conducted in rural communities in Tigray, northern Ethiopia, Silti woreda, Ethiopia, and Pakistan reported no gender difference in the frequency of CL cases [21][22][23].…”
Section: Discussionsupporting
confidence: 92%
“…Our study revealed that males were more affected by CL than females which agree with different studies [10][11][12][13][14][15][16][17]. However, our finding is analogized with the studies reported from Algeria, Istanbul, Turkey, and Larstan, South of Iran that excess in the frequency of CL cases among females than males [18][19][20]. In contrast to this, the studies conducted in rural communities in Tigray, northern Ethiopia, Silti woreda, Ethiopia, and Pakistan reported no gender difference in the frequency of CL cases [21][22][23].…”
Section: Discussionsupporting
confidence: 92%
“…In North African countries, the burden of the disease is high and three Leishmania species, associated to distinct eco-epidemiological patterns, namely L. infantum, L. major and L. tropica, are involved in Leishmania transmission [3][4][5]. However, L. major is by far the most frequent species, with more than 90% of registered cases in Algeria and Tunisia [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Cutaneous leishmaniasis caused by L. major, also known as zoonotic or rural zoonotic cutaneous leishmaniasis (ZCL), is a major public health problem in the North African region, including Tunisia, with thousands of cases occurring each year [5,6]. It is distributed in the arid and Saharan bioclimatic stages, where it follows an epidemic pattern with seasonal occurrence of cases [5,6]. Typical ZCL lesions evolve from papules to nodules to ulcerative lesions, with a central depression and a raised, indurate border [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations